2018
DOI: 10.1007/s00784-018-2401-6
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal and endodontic infectious/inflammatory profile in primary periodontal lesions with secondary endodontic involvement after a calcium hydroxide-based intracanal medication

Abstract: Patients presenting deep probing depth and undergoing periodontal treatment for at least 6 months, with no positive response to periodontal therapy, might benefit with the endodontic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
51
0
18

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(86 citation statements)
references
References 36 publications
17
51
0
18
Order By: Relevance
“…Additionally, with time, periodontal disease can have a degenerative effect on the pulp, including calcifications, fibrosis and collagen resorption, and direct inflammatory effect. 6,18 In the present study, a clinically and radiographically pro- were found in 6 RC with abnormal vital pulp, agreeing with Duque et al, 19 who studied abnormal vital pulp cases associated with periodontal disease.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, with time, periodontal disease can have a degenerative effect on the pulp, including calcifications, fibrosis and collagen resorption, and direct inflammatory effect. 6,18 In the present study, a clinically and radiographically pro- were found in 6 RC with abnormal vital pulp, agreeing with Duque et al, 19 who studied abnormal vital pulp cases associated with periodontal disease.…”
Section: Discussionsupporting
confidence: 92%
“…However, Gram‐negative bacteria were also found, whereas strict anaerobe bacteria were not present. Gram‐positive and facultative anaerobe microorganisms are associated with healthier microbiota and are the first groups of bacteria to colonize the host tissues compared with Gram‐negatives and strict anaerobes, which require longer periods of infection. Therefore, time for RC infection was not enough to harbor greater amounts of Gram‐negative and strict anaerobe bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martinho et al demonstrated that intracanal medicaments (chlorhexidine and calcium hydroxide) reduced bacterial counts and endotoxin levels. Consequently, it was suggested that the reduction of LPS and inflammatory cytokine levels following chemo-mechanical preparation lead to better prognosis of periodontal therapy (27). This established the positive correlations between bacterial counts and inflammatory cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies (26,27) have used similar methodologies to assess the levels of inflammatory mediators and treatment outcomes after root canal treatment. Martinho et al demonstrated that intracanal medicaments (chlorhexidine and calcium hydroxide) reduced bacterial counts and endotoxin levels.…”
Section: Discussionmentioning
confidence: 99%